Effects of Group Living on Pupation in a Lady Beetle - Huston, Miranda; Arnold, Shara; Gordon, Haley; Michaud, J.P.; Marshall, Jeremy (My University, 2018)
To further understand the lives and development habits of insects, we must know how they influence each other through pupation periods. This will ultimately help us understand how interactive insects are throughout their life. To answer this question, we tested the pupation rates of Hippodamia convergens in groups and alone. This will help us delineate the advantages or disadvantages of the organism in groups versus singular pupation. We hypothesized that the Lady Beetles reared alone will develop faster and have a higher growth rate than those reared in groups. During the experiment, the subjects engaged in cannibalism which could have affected our results. Cannibalism occurs when food in the environment is scarce, and although the Lady Beetles were fed, the amounts that were given may not have been proper for their size nor consistent with each group member. At the end of this experiment we saw that the specimens reared in groups pupated more consistently than those reared alone. We assume that the reason Lady Beetles in groups pupated more consistently is because of the stressors in their environment, while the ones alone did not have any stressors. These conclusions may be important because it will help us determine the factors that influence pupation before and during the process in relation to other species of insects.
Keywords: Fall 2018